If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = 6 + -4x Reorder the terms: 2 + 4x = 6 + -4x Solving 2 + 4x = 6 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2 + 4x + 4x = 6 + -4x + 4x Combine like terms: 4x + 4x = 8x 2 + 8x = 6 + -4x + 4x Combine like terms: -4x + 4x = 0 2 + 8x = 6 + 0 2 + 8x = 6 Add '-2' to each side of the equation. 2 + -2 + 8x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 6 + -2 8x = 6 + -2 Combine like terms: 6 + -2 = 4 8x = 4 Divide each side by '8'. x = 0.5 Simplifying x = 0.5
| 2p-2=6 | | 1725+115m=460 | | 14=3y-7 | | 48+48=x | | (2+3i)(4-i)=0 | | -6(7v-5)-3=3(v-6) | | -17=19-12m | | 4x+6=5x-12 | | X+4.5=8.7 | | 0.2x+3=28 | | 1.3+x=-1.6 | | V+6=-12 | | S=52+2.75p | | -1+3(x+2)=5(1+8x) | | -(2y-12+(-y))=-33 | | Y^4+y^3-4y-16=0 | | 5x+12=108-10x | | 1.3+-1.6= | | (4x)-(3x)+(2x)=24 | | 9+2j=5 | | 8m=7(7x-1) | | 18.84=2(3.14) | | 0.3(32)+x=0.3(20+x) | | 11x+45=2x | | (5-6i)(3-2i)=0 | | 3q+10=7 | | 7-(6x+2)=(x-12)+3 | | 2a+9=5a-6 | | x=18-2/3 | | 6+x=54 | | 67-39= | | 9.4=x-17 |